Reactive astrocytes promote adhesive interactions between brain endothelium and endothelial progenitor cells via HMGB1 and beta-2 integrin signaling - Hayakawa, Kazuhide (2013)
Endothelial progenitor cells (EPCs) may contribute to neurovascular repair after stroke and neurodegeneration. A key step in this process should involve adhesive interactions between EPCs and the targeted cerebral endothelium. Here, we tested the hypothesis that reactive astrocytes may play a critical role in enhancing adhesive interactions and transmigration of EPCs across cerebral endothelial cells. Transiently seeding EPCs onto a monolayer of RBE.4 rat brain endothelial cells resulted in a time-dependent adherence between the two cell types. Blocking β2 integrins on EPCs or blocking the receptor for advanced glycation endproducts (RAGE) on endothelial cells significantly decreased EPC-endothelial adherence. Next, we tested whether reactive astrocytes can enhance this process by growing EPCs, brain endothelial cells and astrocytes together in a transwell co-culture system. The presence of reactive astrocytes in the lower chamber significantly promoted adherence between EPCs and endothelial cells in the upper chamber. This process involved the release of soluble HMGB1 from reactive astrocytes that then upregulated endothelial expression of RAGE via Egr1 signaling. Directly adding HMGB1 to the transwell system also promoted EPC-endothelial adhesion and accelerated EPC transmigration into the lower chamber. These initial findings provide proof-of-concept that reactive astrocytes promote crosstalk between cerebral endothelium and EPCs. Further investigation of this phenomenon may lead to a better understanding of cell-cell interactions required for neurovascular recovery after stroke.